TUBUH YANG BERTAHAN: STRATEGI SINDEN MAHASISWA MENGELOLA KRAM DI ATAS PANGGUNG - Anantha Angriany Sitio; Indah Cahyasari; Rudi Punto Prabowo; Bagas Surya Muhammad (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2025)
The purpose of this study is to identify the forms of stage adaptation performed by student sinden (female vocalists in Javanese gamelan) when experiencing leg cramps during a live performance. During performances lasting approximately 40 to 50 minutes, the sinden sit in a static kneeling position, which can lead to muscle tension and cramps in the legs. This condition requires each sinden to develop adaptive strategies to maintain the quality of their vocal and expressive performance despite the physical constraints experienced during the performance. This study employs a qualitative method with a case study approach. The approach was chosen because the research focuses on the phenomenon of cramps experienced by student sinden during recital examinations at the Indonesian Institute of the Arts (ISI) Surakarta. Of the ten sinden who performed, four were selected as research subjects based on varying levels of cramp intensity. In-depth exploration was conducted to reveal their experiences and stage adaptation strategies used to maintain vocal performance and artistic presence amid physical limitations during the performance. The results show four forms of stage adaptation performed by student sinden during the performance: (1) motor stimulation of the right leg, (2) calf muscle stimulation, (3) massage of the calf and shin area, and (4) repositioning of the hands resting on the legs. These adaptations were not performed simultaneously but were adjusted according to each sinden’s physical condition and vocal role. These adaptive activities were generally performed during musical sections without vocals, while during vocal sections, the sinden focused their attention on voice control and musical expression.